Perceptual Organization Based Upon Spatial Relationships in Alzheimer’s Disease - Daniel D. Kurylo; Walter C. Allan; T. Edward Collins; Joshua Baron (Behavioural Neurology)
Alzheimer’s disease (AD) is often accompanied by impaired object recognition, thereby reducing the ability to recognize common objects and familiar faces. Impaired recognition may stem from decreased efficacy in integrating visual information. Studies of perceptual abnormalities in AD indicate an impairment in organizing elements of the visual scene, thereby confusing components of individual forms. This type of impairment is consistent with the characteristics of neural loss, which impact cortical integration. To examine the extent to which perceptual organization is impaired in AD, psychophysical measurements were made of visual perceptual grouping based upon spatial relationships in a group of AD patients and demographically matched elderly control subjects. A comparison was also made between young and elderly control subjects to evaluate the effects of aging on these capacities. Deficits in perceptual organization were found for a subgroup of AD patients, which corresponded to impairment on facial recognition. A less profound functional decline was found for the elderly control group. The degree of impairment for AD subjects did not correlate to level of dementia, but instead appears to be idiosyncratic to individual patients. These results are consistent with impaired integrative function in AD, the degree of which reflects individual differences in the regional distribution of neuropathological changes.